2011
DOI: 10.1103/physrevb.84.224308
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study and modeling of strain-dependent ionic migration in ZrO2

Abstract: Electrolytes with high ionic conductivity at lower temperatures are the prerequisite for the success of Solid Oxide Fuel Cells (SOFC). One promising candidate is doped zirconia. In the past its ionic conductivity has mainly been increased by decreasing its thickness. However, the influence of the thickness is only linear, whereas the impact of migration barriers is exponential. Therefore understanding the oxygen transport in doped zirconia is of fundamental importance. In this work we pursue the approach of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Recently, first-principle calculations have been used to investigate the configuration and stability of the point defects in ZrO 2 [27][28][29], the hydrogen oxidation reactions at the Ni/ZrO 2 interface [30,31], strain-dependent ionic migration in ZrO 2 [32] and ZrO 2 nanosheets and nanotubes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, first-principle calculations have been used to investigate the configuration and stability of the point defects in ZrO 2 [27][28][29], the hydrogen oxidation reactions at the Ni/ZrO 2 interface [30,31], strain-dependent ionic migration in ZrO 2 [32] and ZrO 2 nanosheets and nanotubes [33].…”
Section: Introductionmentioning
confidence: 99%
“…We summarize the E m values of the Fm 3m and the P4 2 /nmc structures obtained herein and in former computational studies 42,[47][48][49][50] in Table 5. Former computational studies have mainly used the GGA, rather than the GGA+U.…”
Section: Crystal Structures With Low E Mmentioning
confidence: 92%
“…4 In some pioneering studies it was shown that strain may positively influence ionic transport, [5][6][7][8] . In a number of subsequent experimental [9][10][11][12][13][14][15] , theoretical studies [16][17][18][19][20][21][22][23] and a few reviews 4,21,24-26 intrinsic strain as a control parameter has been investigated and even used to tune transport properties in oxide ceramic multilayer microdots. 27 Mostly, epitaxial strain originating at heterophase boundaries was considered, but uniaxially strained single crystals were also studied as well defined model systems.…”
Section: Strain As An "Issue" and As A Conceptmentioning
confidence: 99%